HIV Exploits Antiviral Host Innate GCN2-ATF4 Signaling for Establishing Viral Replication Early in Infection - Guochun Jiang (American Society for Microbiology, 2017)
ABSTRACT Antiviral innate host defenses against acute viral infections include suppression of host protein synthesis to restrict viral protein production. Less is known about mechanisms by which viral pathogens subvert host antiviral innate responses for establishing their replication and dissemination. We investigated early innate defense against human immunodeficiency virus (HIV) infection and viral evasion by utilizing human CD4+ T cell cultures in vitro and a simian immunodeficiency virus (SIV) model of AIDS in vivo. Our data showed that early host innate defense against the viral infection involves GCN2-ATF4 signaling-mediated suppression of global protein synthesis, which is exploited by the virus for supporting its own replication during early viral infection and dissemination in the gut mucosa. Suppression of protein synthesis and induction of protein kinase GCN2-ATF4 signaling were detected in the gut during acute SIV infection. These changes diminished during chronic viral infection. HIV replication induced by serum deprivation in CD4+ T cells was linked to the induction of ATF4 that was recruited to the HIV long terminal repeat (LTR) to promote viral transcription. Experimental inhibition of GCN2-ATF4 signaling either by a specific inhibitor or by amino acid supplementation suppressed the induction of HIV expression. Enhancing ATF4 expression through selenium administration resulted in reactivation of latent HIV in vitro as well as ex vivo in the primary CD4+ T cells isolated from patients receiving suppressive antiretroviral therapy (ART). In summary, HIV/SIV exploits the early host antiviral response through GCN2-ATF4 signaling by utilizing ATF4 for activating the viral LTR transcription to establish initial viral replication and is a potential target for HIV prevention and therapy. IMPORTANCE Understanding how HIV overcomes host antiviral innate defense response in order to establish infection and dissemination is critical for developing prevention and treatment strategies. Most investigations focused on the viral pathogenic mechanisms leading to immune dysfunction following robust viral infection and dissemination. Less is known about mechanisms that enable HIV to establish its presence despite rapid onset of host antiviral innate response. Our novel findings provide insights into the viral strategy that hijacks the host innate response of the suppression of protein biosynthesis to restrict the virus production. The virus leverages transcription factor ATF4 expression during the GCN2-ATF4 signaling response and utilizes it to activate viral transcription through the LTR to support viral transcription and production in both HIV and SIV infections. This unique viral strategy is exploiting the innate response and is distinct from the mechanisms of immune dysfunction after the critical mass of viral loads is generated.